Use, maintenance and dose effects of cognitive speed of processing training in Parkinson's disease. (3rd October 2017) - Valdés, Elise G.; O'Connor, Melissa L.; Uc, Ergun Y.; Hauser, Robert A.; Andel, Ross; Edwards, Jerri D.
ABSTRACT: Introduction: Recent research indicated that cognitive speed of processing training (SPT) improved Useful Field of View (UFOV) among individuals with Parkinson's disease (PD). The effects of SPT in PD have not been further examined. The objectives of the current study were to investigate use, maintenance and dose effects of SPT among individuals with PD. Methods: Participants who were randomized to SPT or a delayed control group completed the UFOV at a six-month follow-up visit. Use of SPT was monitored across the six-month study period. Regression explored factors affecting SPT use. Mixed effect models were conducted to examine the durability of training gains among those randomized to SPT ( n = 44), and training dose effects among the entire sample ( n = 87). Results: The majority of participants chose to continue to use SPT (52%). Those randomized to SPT maintained improvements in UFOV performance. A significant dose effect of SPT was evident such that more hours of training were associated with greater UFOV performance improvements. The cognitive benefits derived from SPT in PD may be maintained for up to three months. Conclusion: Future research should determine how long gains endure and explore if such training gains transfer.